STUDY OF FLOODING IN THE PANDANWANGI AREA IN WATERSHED KALISARI USING SWMM 5.1 APPLICATION - Mohammad Zainul Arif Arif; Winda Harsanti (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
This study focuses on flooding issues in Pandanwangi area, particularly at the LA Sucipto-Gang Makam intersection in Malang City, which is part of the Kalisari watershed. Due to rapid urban development, the percentage of flooding has increased, possibly due to inadequate drainage or drainage systems that are unable to accommodate continuous rainfall. It is necessary to analyze the exact causes of flooding, therefore this study aims to analyze flood discharge using Gumbel Method, existing channel capacity, calculate the budget plan for redesign, and determine the influence of the watershed area on the Kalisari River Basin. The analysis methods used are hydrological and hydraulic analysis for calculations using three rainfall stations: Ciliwung, Singosari, and Jabung. Flood flow analysis and modeling are conducted using the EPA SWMM 5.1 application. Calculations for existing channels and redesign must be controlled to ensure that the calculations are accurate. Results After calculating the 10-year design rainfall using the Gumbel method, the result was 106.752 mm/day. Analysis using SWMM 5.1 software and calculations for existing channels and redesign revealed flooding from point S-R to point O-N. The new dimensions capable of accommodating flood discharge are a height of 1.2 m and a width of 0.4 m. The estimated budget for the redesign at that point is approximately Rp. 189,075,905.55.